P108/O28 Fatty acid oxidation can drive human monocyte derived CCL20 in the RA synovial environment. (March 2019) - Rodgers, LC; Cole, J; Rattigan, K; Barrett, MP; Kurian, N; McInnes, IB; Goodyear, CS
Abstract : Career situation of first and presenting author: Post-doctoral fellow. Introduction: Metabolic pathways are considered to have a governing role in inflammatory cascades in myeloid cells. This is particularly evident in murine macrophages where glycolysis and fatty acid oxidation (FAO) have been implicated in inflammatory cascades and immune regulation respectively. 1 However, investigation of intracellular metabolism of human monocytes in the context of the hypoxic and inflammatory RA synovium is lacking. Objectives: To mimic the hypoxic RA environment in vitro and metabolically profile human monocytes. Determine if altered metabolic pathways have a functional impact on monocytes under disease-relevant conditions. Methods: Human monocytes were isolated from buffy coats and were exposed to hypoxia in vitro . Metabolic profiling of monocytes was carried out by LC-MS metabolomics. Inflammatory mediator release after LPS or RA-synovial fluid (RA-SF) stimulation was analysed by ELISA. FAO was inhibited by etomoxir or enhanced with exogenous carnitine supplements. Transcriptomics of RA blood monocytes and RA-SF macrophages was carried out by microarray. Results: We report that hypoxia exacerbates CCL20 and IL-1β release in response to LPS and increases glycolytic intermediates at the expense of carnitines. Modulation of carnitine identified a novel role for FAO in the production of CCL20 in response to LPS. Transcriptomics of RA blood monocytes and RA-SF macrophages revealed that fatty acid metabolism was altered and CCL20 was increased when monocytes enter the RA milieu. In vitro analysis of monocytes showed that RA-SF increases carnitine abundance and CCL20 production in hypoxia, which was exacerbated by exogenous carnitine. Conclusions: This work has revealed a novel inflammatory mechanism in RA which links FAO to CCL20 production in human monocytes. This may contribute to RA disease pathogenesis by promoting the recruitment of Th17 cells and osteoclastogenesis. 2 3 References: O'Neill LA, et al. Nat Rev Immunol 2016;16:553–565. Hirota K, et al. J Exp Med 2007;204:2803–2812. Lisignoli G, et al. J Cell Physiol 2009;221:154–160. Disclosure of Interest: None declared.